Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Pegawai - Sulastiningsih, Sulastiningsih; Ambarwati, Lilik (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2015)
The influence of budget participation has attracted the attention of researchers in recent years. Some research of the relation of budget participation on employee performance indicate inconsistent results. This study aims to know the influence of budget participation to employee performance. The respondent are employee that participate in the preparation of the budget, including middle managers and lower managers. The data is obtained through questionnaires to 30 employees. The model analysis is a simple linear regression. The results of this study indicate budgetary participation influence to employee performance. This study also found that budget participation has a positive effect on employee performance.Key Word : budget participation, employee performance